The KOMPONEN PERTUMBUHAN DAN HASIL PRODUKTIVITAS TIGA VARIETAS JAGUNG (Zea mays L) TERHADAP CEKAMAN KEKERINGAN MELALUI FREKUENSI PEMBERIAN AIR - Arsa, IGB Adwita; Dato, Calvin Dewa; Kasim, Muhamad (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
The purpose of this research is to determine the growth components and productivity of three corn varieties (Zea mays L.) in response to the frequency of water irrigation. The treatments were arranged in a two-factor factorial design within a Randomized Complete Block Design (RCBD). The first factor was the frequency of water irrigation, consisting of 3 treatment levels: once a day (F1), every 2 days (F2), and every 3 days (F3). The second factor was the variety factor (V), comprising 3 varieties: Bonanza F1, hybrid variety Pertiwi 5, and variety Bisi 18, resulting in 9 treatment combinations. Each treatment was replicated three times, yielding a total of 27 experimental units. The parameters observed in this study included plant height, leaf count, stem diameter, flowering age, cob length, cob diameter, and cob fresh weight. The results of the research indicate that the frequency of water irrigation significantly affects the leaf count at 14 days after sowing (HST), stem diameter, cob length, cob diameter, and cob fresh weight. Meanwhile, the variety factor significantly influences plant height and leaf count at 14 HST and post-flowering, stem diameter, cob diameter, and cob fresh weight. The interaction between the frequency of water irrigation and variety has a significant impact on stem diameter, cob diameter, and cob fresh weight. The best varieties for all frequencies of water irrigation are Pertiwi-5, and varieties tolerant to drought stress are Pertiwi-5 and Bisi-18.